Molecular Strategies for Intensity-Dependent Olfactory Processing in Caenorhabditis elegans - Cheng, Hankui; Liu, Yu; Xue, Yadan; Shao, Jiajie; Tan, Zhibing; Liu, Siyan; Duan, Shumin; Kang, Lijun (Frontiers in Molecular Neuroscience, 2021)
Various odorants trigger complex animal behaviors across species in both quality- and quantity-dependent manners. However, how the intensity of olfactory input is encoded remains largely unknown. Here we revealed that both high and low concentrations of isoamyl alcohol (IAA) induce bi-directional currents through a Gα- guanylate cyclase (GC)- cGMP signaling pathway in C. elegans olfactory neuron AWC, while two opposite cGMP signaling pathways are responsible for odor-sensing in olfactory neuron AWB: 1) a depolarizing Gα (GPA-3)- phosphodiesterase (PDE) - cGMP pathway which can be activated by low concentrations of isoamyl alcohol (IAA), and 2) a hyperpolarizing Gα (ODR-3)- GC- cGMP pathway sensing high concentrations of IAA. Besides, IAA induced Gα (ODR-3)-TRPV(OSM-9)-dependent currents in AWA and ASH neurons with different thresholds. Our results demonstrate that an elaborate combination of multiple signaling machineries encode the intensity of olfactory input, shedding light on understanding the molecular strategies on sensory transduction.